MRI features of inflammatory hepatocellular adenomas on hepatocyte phase imaging with liver‐specific contrast agents. Issue 5 (29th July 2013) - Thomeer, Maarten G.; Willemssen, Francois E.; Biermann, Katharina K.; El Addouli, Haroun; de Man, Rob A.; Ijzermans, Jan N.; Dwarkasing, Roy S.
Abstract : Purpose: To evaluate the presentation of inflammatory hepatocellular adenomas (HCAs) on hepatocyte phase MRI. Materials and Methods: We retrospectively reviewed the MRI features of histologically proven HCAs on hepatocyte phase imaging. Twenty‐one lesions (17 with inflammatory subtype) were scanned with gadobenate dimeglumine. Signal intensities of the lesions were assessed in the hepatocyte phase and on the T1‐weighted sequences before contrast. Results: After gadobenate dimeglumine injection, 71% (12/17) of the inflammatory HCAs showed areas of iso‐ or hyperintensity to the surrounding liver in the hepatocyte phase. In 82% (10/12) of the iso‐ or hyperintense lesions, this was found over more than 75% of the lesion surface. None of the noninflammatory HCAs showed areas of iso‐ or hyperintensity to the surrounding liver in the hepatocyte phase. From these 12, 7 were hyperintense on T1‐weighting before contrast due to liver steatosis, 2 due to intrinsic hyperintensity (on the in‐phase sequence), and 3 were isointense. Conclusion: In contrast to noninflammatory HCAs, inflammatory HCAs can show areas of iso‐ to hyperintensity to the surrounding liver in the hepatocyte phase; therefore, other typical imaging features should also be used to distinguish between HCAs and FNHs.J. Magn. Reson. Imaging 2014;39:1259–1264 . ©2013 Wiley Periodicals, Inc .